Diversity and Potential of Undergrowth as Traditional Medicine in Sangtandung Village, North Walenrang sub district, Luwu - Liana Liana; Olifia Monika Pasambo; Maria Maria; Novi Herman Sada; Ayub ayub (Universitas Andi Djemma Palopo, 2023)
The use of undergrowth as medicine has been carried out by many people, especially traditional communities who live far from health services whose use has been passed down from generation to generation. Attention to traditional medicines has shown an increase, this is evident from the use of natural medicine in developed countries reaching 65% while it is estimated that there are 9,600 plant species that have been utilized by 400 various ethnic or ethnic groups in Indonesia. Therefore, this study aims to determine the potential of the undergrowth used as traditional medicine in Sangtandung Village, North Walenrang District, Luwu Regency. There are two stages in this research, namely for species diversity using the method of determining plots for collecting data on species diversity, while the potential for medicine use uses an interview method with respondents who have been determined using a purposive sampling method. Data analysis for species diversity used is an important value index analysis by calculating the values of density, relative density, frequency, relative frequency, while for the potential of undergrowth as medicine using quantitative descriptive analysis. The results showed that there were 18 types of undergrowth identified as potential as traditional medicine in Sangtandung Village and the embarrassed daughter plant (Mimosa pudica Lin) had the highest IVI. Of the total 18 types of undergrowth that have the potential to be used as traditional medicine, there are 9 types that have been used by the community as medicine and 9 types that have not been utilized by the people of Sangtandung Village. Among them are putrimalu (Mimosa pudica Lin), urang aring (Eclita prostrate), sidaguri ( Sida rhombifolia), pakis (Polypodiophyta), bayam duri (Amaranthus Spinosus), bayam malabar (Basella alba), cakar ayam (Selaginella doederleinii), meniran (Phyllanthus urinaria), and gelinggang (Cassia Alata). Generally, the leaves are used by boiling and drinking the boiled water to treat various diseases.